![1.\;(x^{-2}-1)^{-1}\geq1\\ \frac1{x^{-2}-1}\geq1\\ \frac1{\frac1{x^2}-1}\geq1\\ \frac1{\frac{1-x^2}{x^2}}\geq1\\ \frac{x^2}{1-x^2}\geq1\\ x^2\geq1-x^2\\ 2x^2\geq1\\ x^2\geq\frac12\\ \begin{cases} x\geq\frac1{\sqrt2}\\ x\leq-\frac1{\sqrt2} \end{cases} 1.\;(x^{-2}-1)^{-1}\geq1\\ \frac1{x^{-2}-1}\geq1\\ \frac1{\frac1{x^2}-1}\geq1\\ \frac1{\frac{1-x^2}{x^2}}\geq1\\ \frac{x^2}{1-x^2}\geq1\\ x^2\geq1-x^2\\ 2x^2\geq1\\ x^2\geq\frac12\\ \begin{cases} x\geq\frac1{\sqrt2}\\ x\leq-\frac1{\sqrt2} \end{cases}](https://tex.z-dn.net/?f=1.%5C%3B%28x%5E%7B-2%7D-1%29%5E%7B-1%7D%5Cgeq1%5C%5C+%5Cfrac1%7Bx%5E%7B-2%7D-1%7D%5Cgeq1%5C%5C+%5Cfrac1%7B%5Cfrac1%7Bx%5E2%7D-1%7D%5Cgeq1%5C%5C+%5Cfrac1%7B%5Cfrac%7B1-x%5E2%7D%7Bx%5E2%7D%7D%5Cgeq1%5C%5C+%5Cfrac%7Bx%5E2%7D%7B1-x%5E2%7D%5Cgeq1%5C%5C+x%5E2%5Cgeq1-x%5E2%5C%5C+2x%5E2%5Cgeq1%5C%5C+x%5E2%5Cgeq%5Cfrac12%5C%5C+%5Cbegin%7Bcases%7D+x%5Cgeq%5Cfrac1%7B%5Csqrt2%7D%5C%5C+x%5Cleq-%5Cfrac1%7B%5Csqrt2%7D+%5Cend%7Bcases%7D)
![2.\;\frac1{x-2}-\frac1{x-3}\geq1\\ \frac{x-3-x+2}{(x-2)(x-3)}\geq1\\ \frac{-1}{x^2-5x+6}\geq1\\ -1\geq x^2-5x+6\\ x^2-5x+7\leq0\\ x^2-5x+7=0\\ D=25-4\cdot7=25-28=-3<0\;pew.\;HET 2.\;\frac1{x-2}-\frac1{x-3}\geq1\\ \frac{x-3-x+2}{(x-2)(x-3)}\geq1\\ \frac{-1}{x^2-5x+6}\geq1\\ -1\geq x^2-5x+6\\ x^2-5x+7\leq0\\ x^2-5x+7=0\\ D=25-4\cdot7=25-28=-3<0\;pew.\;HET](https://tex.z-dn.net/?f=2.%5C%3B%5Cfrac1%7Bx-2%7D-%5Cfrac1%7Bx-3%7D%5Cgeq1%5C%5C+%5Cfrac%7Bx-3-x%2B2%7D%7B%28x-2%29%28x-3%29%7D%5Cgeq1%5C%5C+%5Cfrac%7B-1%7D%7Bx%5E2-5x%2B6%7D%5Cgeq1%5C%5C+-1%5Cgeq+x%5E2-5x%2B6%5C%5C+x%5E2-5x%2B7%5Cleq0%5C%5C+x%5E2-5x%2B7%3D0%5C%5C+D%3D25-4%5Ccdot7%3D25-28%3D-3%3C0%5C%3Bpew.%5C%3BHET)
0\\ x=0\Rightarrow 2(0)^2+3(0)-2=-2<0\\ x=2\Rightarrow 2(3)^2+3(3)-2=25>0\\ x\in[-4;\;1]" alt="3.\;\frac2x\leq2+\frac3{x+1}\\ O.D.3.:\\ \begin{cases} \x\neq0\\ x+1\neq0 \end{cases}\Rightarrow \begin{cases} \x\neq0\\ x\neq-1 \end{cases} \frac2x\leq\frac{2x+2+3}{x+1}\\ \frac2x\leq\frac{2x+5}{x+1}\\ 2x+2\leq2x^2+5x\\ 2x^2+3x-2\geq0\\ 2x^2+3x-2=0\\ D=9+4\cdot2\cdot2=25\\ x_1=1,\;x_2=-4\\ x=-5\Rightarrow 2(-5)^2+3(-5)-2=33>0\\ x=0\Rightarrow 2(0)^2+3(0)-2=-2<0\\ x=2\Rightarrow 2(3)^2+3(3)-2=25>0\\ x\in[-4;\;1]" align="absmiddle" class="latex-formula">